2012
DOI: 10.1007/s00125-012-2686-y
|View full text |Cite|
|
Sign up to set email alerts
|

A high-fat-diet-induced cognitive deficit in rats that is not prevented by improving insulin sensitivity with metformin

Abstract: Aims/hypothesis We previously demonstrated that animals fed a high-fat (HF) diet for 10 weeks developed insulin resistance and behavioural inflexibility. We hypothesised that intervention with metformin would diminish the HF-feedingevoked cognitive deficit by improving insulin sensitivity. Methods Rats were trained in an operant-based matching and non-matching to position task (MTP/NMTP). Animals received an HF (45% of kJ as lard; n024), standard chow (SC; n016), HF + metformin (144 mg/kg in diet; n020) or SC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 48 publications
4
47
0
Order By: Relevance
“…In obese, leptin resistant (db/db) mice, metformin has been shown to attenuate the increase of total tau and phospho-tau, the reduction of synaptophysin, and the decreased of AÎČ level; however, it does not attenuate the impairments of spatial learning and memory as well as long-term hyperglycemia (Li et al, 2012). This result is similar to that of another study, which reports that metformin prevent metabolic but not cognitive deficits Brought to you by | HEC Bibliotheque Maryriam ET J. Authenticated Download Date | 6/9/15 3:18 AM associated with high-fat feeding (McNeilly et al, 2012). However, novel drug treatments for type 2 diabetes with glucagon-like peptide-1 (GLP-1) analogs have shown superior neuroprotective effects.…”
Section: Therapeutic Methodologies Tested On Animal Modelssupporting
confidence: 90%
See 1 more Smart Citation
“…In obese, leptin resistant (db/db) mice, metformin has been shown to attenuate the increase of total tau and phospho-tau, the reduction of synaptophysin, and the decreased of AÎČ level; however, it does not attenuate the impairments of spatial learning and memory as well as long-term hyperglycemia (Li et al, 2012). This result is similar to that of another study, which reports that metformin prevent metabolic but not cognitive deficits Brought to you by | HEC Bibliotheque Maryriam ET J. Authenticated Download Date | 6/9/15 3:18 AM associated with high-fat feeding (McNeilly et al, 2012). However, novel drug treatments for type 2 diabetes with glucagon-like peptide-1 (GLP-1) analogs have shown superior neuroprotective effects.…”
Section: Therapeutic Methodologies Tested On Animal Modelssupporting
confidence: 90%
“…It has been shown that animals receiving high-fat (HF)/low carbohydrate (LC) food could increase brain levels of soluble AÎČ (Pedrini et al, 2009). Rats receiving an HF diet for 10 weeks develop both insulin resistance and cognitive deficits; however, contrary to expectation, re-sensitizing insulin signaling in the periphery with metformin does not improve the learning and memory impairment (McNeilly et al, 2012). In a transgenic animal model of AD, impaired learning and memory of mice overexpressing mutant amyloid precursor protein (APP) and presenilin-1 (PS1dE9) are exacerbated by HF diet treatment.…”
Section: High-fat Diet Induced Rodents With Cognitive Impairmentsmentioning
confidence: 94%
“…Lard is one of the most widely consumed foods rich in saturated fatty acids, and it is often chosen to observe the deleterious effects of a high-fat diet [20,[23][24][25] . In this study, we used standard rodent chow supplemented with lard alone, independent of other hyperlipidemia-inducing components, such as cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…High fat feeding can produce behavioural changes in rodents before the development of T2DM, which are also independent of increased insulin resistance (McNeilly et al, 2011(McNeilly et al, , 2012. Other studies have shown that chronic HF feeding for 6 weeks reduces 5-hydroxytryptamine (5-HT) release and turnover in the hypothalamus and hippocampus of rodents (Pissios and Maratos-Flier, 2007).…”
Section: Introductionmentioning
confidence: 98%